How Does Group Climate Foster or Hinder Employee Voice? A Cross-Level Examination - Qian, Xiaoye; Li, Qian; Wang, Jue; Gong, Shiyang; Zhou, Hao (Frontiers in Psychology, 2021)
Although empirical evidence has accumulated showing that group climate has a significant impact on employee voice, knowledge about how different types of climates may influence voice is limited. Drawing upon the theory of planned behavior, we develop and test a model that explains whether and how the two group climates, cooperation climate and sanction climate, differentially predict employee promotive and prohibitive voice. We test the hypotheses using data collected from a sample of 274 full-time employees nested in 58 workgroups across two time periods. The empirical results show that group climate predicts employee voice in different ways: group cooperation climate has a positive effect on both types of employee voice, whereas group sanction climate shows a negative effect on promotive voice. Individuals’ psychological capital is a cross-level mediator in the relationship between group climate and employee voice. Employees’ prevention focus negatively moderates the relationship between psychological capital and employee voice. These results highlight the important effect of group climate on employee voice in organization and calls on managers to create a favorable environment to increase employees’ psychological capital and voice behaviors.